2013
DOI: 10.1002/asia.201300869
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Peripherally Nitrated, Aminated, and Arylaminated Subporphyrins

Abstract: 2-Nitro-5,10,15-tri(4-tert-butylphenyl)subporphyrin 2 was prepared by the nitration of 5,10,15-tri(4-tert- butylphenyl)subporphyrin 1a with five equivalents of Cu(NO3)2·5H2O in a mixed EtOAc/Ac2O solution and was reduced into 2-amino-5,10,15-tri(4-tert-butylphenyl)subporphyrin 3. Bromination of 5,10,15-triphenylsubporphyrin 1b with 1.5 equivalents of N-bromosuccinimide (NBS) gave 2-bromo-5,10,15-triphenylsubporphyrin, which was converted into various 2-arylamino-5,10,15-triphenylsubporphyrins (4a-4d) and 2-ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…Previously, meso ‐triphenylsubporphyrin B ‐methoxide was nitrated with Cu(NO 3 ) 2 to give a β‐nitrated compound in good yield. However nitration of meso ‐free subporphyrin 8 with Cu(NO 3 ) 2 gave an almost inseparable mixture of mono‐ and di‐nitrated subporphyrins . We found that nitration of 8 with AgNO 2 and I 2 in CH 2 Cl 2 /MeCN was slow but gave meso ‐nitrosubporphyrin 9 selectively in 71 % yield after stirring for 12 h at room temperature (Scheme ).…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…Previously, meso ‐triphenylsubporphyrin B ‐methoxide was nitrated with Cu(NO 3 ) 2 to give a β‐nitrated compound in good yield. However nitration of meso ‐free subporphyrin 8 with Cu(NO 3 ) 2 gave an almost inseparable mixture of mono‐ and di‐nitrated subporphyrins . We found that nitration of 8 with AgNO 2 and I 2 in CH 2 Cl 2 /MeCN was slow but gave meso ‐nitrosubporphyrin 9 selectively in 71 % yield after stirring for 12 h at room temperature (Scheme ).…”
Section: Resultsmentioning
confidence: 84%
“…Reduction of 9 with NaBH 4 and Pd/C quantitatively gave meso ‐aminosubporphyrin 10 . Notably, 10 was obtained as fairly stable solid, while β‐aminosubporphyrin was reported to be unstable on silica gel . Finally, oxidation of 10 was attempted with PbO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking advantage of this feature, many interesting examples have been explored. β‐Substituted subporphyrins have been also developed, such as β‐halogenated, β‐nitrated, β‐aminated, and β‐sulfanylated subporphyrins . But there are only limited examples of β‐π‐extended subporphyrins and only tribenzosubporphines 1 and meso ‐triphenyl‐tribenzosubporphyrins 2 were reported .…”
Section: Methodsmentioning
confidence: 99%